'Sustainable' Discourse: A Critical Analysis of the 2030 Agenda for Sustainable Development. (December 2019) - Ala-Uddin, Mohammad
Sustainability is a catchphrase in contemporary theory and practice of international development. It has become an epicentre of development debate following the adoption of the Sustainable Development Goals (SDGs) in 2015 by the United Nations (UN). Many view the new set of goals as a significant step in the field of development, but scholars and practitioners still grapple with reaching a consensus on a common definition of sustainability. This article problematizes the notion and theoretical underpinning of sustainability. The author focusses on the discursive practices that played a dominant role in shaping the conception of sustainability, especially within the formation of the SDGs. Using the three-dimensional analytical framework of discourse studies outlined by Fairclough (1995, Critical discourse analysis, Boston, MA: Addison Wesley), the author interprets the text of the SDGs at micro level (discourse), meso level (discursive practices) and macro level (discursive events).